(untitled) (Bangladesh Journal of Botany, 2013)
Microbial quality of common salad vegetables (viz. carrot, cucumber, tomato and lettuce) collected from Dhaka metropolis was analysed to detect the presence of bacterial pathogens. The occurrence of huge numbers of fecal coliforms (1.0×104 - 4.09×106 cfu/g), Escherichia coli (1.0×104 - 5.0×108 cfu/g), Staphylococcus aureus (2.0×105 - 5.95×107 cfu/g), and Listeria spp. (1.5×106 - 6.5×107 cfu/g) were detected in all the tested samples. Interestingly, occurrence of viable but non-culturable (VBNC) bacteria was also noticed. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13442 Bangladesh J. Bot. 41(2): 159-162, 2012 (December)